Mandatory IFRS Adoption in Transition Economy with Weak Enforcement Environment and Long-Term Disclosure Quality: Array - Atanasovski, Atanasko; Trpeska, Marina (The Journal of Accounting and Management, 2020)
This paper examines the mandatory compliance with IFRS disclosure requirements for listed companies in Macedonia, developing middle-income country with less developed capital market and weak enforcement environment for financial reporting. This transition economy introduced IFRS in 1998 and the study was conducted on a sample of 90 companies that applied IFRS’s in their 2017 financial statements. We constructed both weighted and unweighted disclosure indices to measure the degree of compliance. The level of compliance was significantly greater for companies engaging international audit network firm and companies that were more leveraged. The findings did not support theories explaining compliance in developed capital markets and in countries with strong enforcement environment for financial reporting.